Expand the formula (a-b)^2

(a – b)2 = a2 – 2ab + b2

Solution

(a – b)2 let us derive the equation

Let us start with LHS: (a – b)2

(a-b)2 = (a-b) (a+b)

By distributive law

(a-b)2= a (a-b) b (a+b)

Then again by multiplying each term we get,

(a-b)2= a2 – ab –ab + b2

(a-b)2= a2 – 2ab + b2

Answer

(a-b)2= a2 – 2ab + b2

Was this answer helpful?

  
   

0 (0)

Upvote (0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question